NKRI Harga Mati: Tinjauan Al-Qur’an Terhadap Urgensi Persatuan di Tengah Kebinekaan - Eko Zulfikar; Abdul Kher; Lukman Nul Hakim; Rahmat Hidayat; Muhajirin Muhajirin (Jurnal Semiotika Quran, 2023)
This article attempts to review the Qur'anic review of the urgency of unity in the midst of diversity by reflecting on the Unitary State of the Republic of Indonesia, the price of death for the Indonesian people. By using descriptive analytical qualitative methods, it can be concluded that diversity and diversity in Indonesia is a necessity. Therefore, Islam has encouraged its adherents to love and tolerate each other, to knit the ties of ukhuwah basyariyah and to build harmonious relations between human beings despite different religions, races, ethnicities, and others. In the view of the Qur'an, diversity and diversity can actually be a rope of unity and not be a way of division that can bring down each other and cause war in a country. The expression of the Qur'an is closely related to diversity and diversity in line with the slogan of the Unitary State of the Republic of Indonesia Price Mati, because it has become the foundation of unity in the midst of diversity in Indonesia